LEGAL ASPECT OF THE FOREIGN FRANCHAISE PROTECTION IN INDONESIAN BUSINESS DEVELOPMENT - Amiruddin, Novendri; Annisa, Rizki Nur; Putra, Bouwris Charisma (Faculty of Law, Universitas Sebelas Maret, 2017)
This study aimed to study the Legal Protection For Foreign FranchiseeFrom The Existence Of High Levels Of Foreign Business In Indonesia. By using a doctrinal or normative study which assemble of primary data and secondary data. The concept of franchisee business has been one discussed topic that provides new breakthrough upon Indonesian economic dynamics, especially upon the form of commerce development, considering franchise as a successful business. Law protection against foreign franchiseebusiness in indonesia has resulted many regulation but franchisee agreement is the point to give legal protection for franchisee.